Anticoagulants Interfere With the Angiogenic and Regenerative Responses Mediated by Platelets - Oneto, Paula; Zubiry, Paula Romina; Schattner, Mirta; Etulain, Julia (Frontiers in Bioengineering and Biotechnology, 2020)
Background and aims. Platelet rich plasma (PRP) obtained from blood anticoagulated with acid-citrate-dextrose (ACD) or sodium-citrate (SC) is used for regenerative medicine as source of platelet-derived growth factors. Allergic reactions against citrate were reported in patients after local injection of PRP allowing us to hypothesize that anticoagulants exert a harmful and local effect that interferes with the regenerative proprieties of platelets. Herein we test this hypothesis by analyzing the effect of ACD and SC on angiogenic and regenerative responses mediated by platelets. Methods. PRP was obtained from SC- or ACD-anticoagulated blood; platelets were lysed to release growth factors; and PRP releasates (PRPr) were used to induce in vitro endothelial proliferation and 2D-migration, and regeneration of mouse skin wounds. Results. We first compared proliferation and migration of endothelial cells mediated by anticoagulated-PRPr supplemented or not with CaCl2. Alteration of endothelial adhesion and impediment of proliferation and migration was observed without CaCl2. Although endothelial morphology was normalized in SC- and ACD-PRPr after calcium restitution, angiogenic responses were only markedly induced by SC-PRPr. In vivo studies revealed a delay in mouse skin regeneration after treatment with anticoagulated-PRPr without CaCl2. Healing was only induced after calcium restitution in SC- but ACD-PRPr. Moreover, the development of inflammatory intradermal papules was evidenced after injection of ACD-PRPr. Supplementation of SC-PRPr with the equivalent concentration of dextrose (D-Glucose, 18mM) present in ACD-PRPr resulted in reduction of endothelial proliferation and migration, delay of mouse skin regeneration and development of intradermal papules. Finally, collecting blood with half amount of SC significantly improved all the angiogenic and regenerative responses mediated by PRPr. In contrast, the delay of skin regeneration and the development of inflammatory papules remained stable after dilution of ACD. Conclusions. Our findings indicate that 1) calcium restitution is required to impair the cellular and tissue alterations induced by citrated-anticoagulants contained in PRP; 2) ACD-derived dextrose confers anti-angiogenic, anti-regenerative and pro-inflammatory proprieties to PRP; and 3) half concentration of SC improves the angiogenesis and regeneration mediated by PRP.